2014
DOI: 10.1017/s000711451400292x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of in vivo amino acid kinetics facilitates increased amino acid availability for fetal growth in adolescent and adult pregnancies alike

Abstract: During pregnancy, adult women with a normal BMI synthesise extra amino acids after an overnight fast by increasing body protein breakdown and decreasing amino acid oxidation. It is not known whether adolescent girls can make these adaptations during pregnancy. The present study aimed to measure and compare the protein, glutamine and alanine kinetics of adult women and adolescent girls at early-, mid-and late-pregnancy. Kinetics were measured in the overnight fasted state using intravenous infusions of N 2 -ure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
1
3
0
1
Order By: Relevance
“…The authors suggested that the lower serine kinetics in late pregnancy may be part of a general down-regulation of α-amino N turnover related to a decreased rate of branchedchain amino acid transamination to facilitate N conservation and accretion. In agreement, in an earlier report of data from this project (11) , urea flux, an index of protein and amino acid catabolism, decreased from the first to the third trimester in both pregnant adolescent girls and adult women, indicating that they were conserving more N in the third trimester. However, leucine oxidation in the third trimester was similar to the first trimester, which does not support a decrease in branched-chain amino acid transamination in late pregnancy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The authors suggested that the lower serine kinetics in late pregnancy may be part of a general down-regulation of α-amino N turnover related to a decreased rate of branchedchain amino acid transamination to facilitate N conservation and accretion. In agreement, in an earlier report of data from this project (11) , urea flux, an index of protein and amino acid catabolism, decreased from the first to the third trimester in both pregnant adolescent girls and adult women, indicating that they were conserving more N in the third trimester. However, leucine oxidation in the third trimester was similar to the first trimester, which does not support a decrease in branched-chain amino acid transamination in late pregnancy.…”
Section: Discussionsupporting
confidence: 92%
“…The maternal characteristics and pregnancy outcomes of the subjects have been published previously ( 11 ) . However, for convenience, some of the relevant data are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, amino acid kinetics studies suggest that adolescents may be less able than older women to increase their circulating amino acid concentration through synthesis and/or protein breakdown in response to pregnancy. 22,23 This could reduce the availability of the amino acids to the fetus, especially in late pregnancy when requirements are greatest to support rapid fetal growth. This mechanism does not explain the findings in early pregnancy when fetal nutrient requirements are small.…”
Section: Discussionmentioning
confidence: 99%
“…Важную роль в биохимических процессах организма человека занимают аминокислоты [4][5][6]15]. Возрастание роли аминокислот при беременности связано с повышенной потребностью белка для обеспечения материнских тканей и роста плода, необходимостью поддержания доступности глюкозы -основного топлива для растущего плода [14], а также участием их в регуляторно-метаболических процессах, направленных на обеспечение роста и нормальных физиологических функций плода [13]. Содержание аминокислот в сыворотке крови матери изменяется при развитии осложнений беременности, характер изменений определяется патологией [7][8][9], поэтому исследование метаболического профиля биологических жидкостей и выявление его особенностей у беременных женщин, имеющих нарушения гестационного процесса, является важным для разработки новых эффективных подходов к раннему прогнозированию осложнений и более глубокому пониманию их патогенеза [9].…”
Section: Introductionunclassified